2021
DOI: 10.1007/s40201-021-00637-6
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of obsterics and gynecology hospital air by bacterial and fungal aerosols associated with nosocomial infections

Abstract: Bacterial and fungal bioaerosols are a global concern due to nosocomial infections, especially in developing countries. Our study aimed to detect fungal and bacterial bioaerosols in different wards of an obstetrics and gynecology hospital air samples. 240 bioaerosol samples were collected by performing impaction method from different wards of a hospital in the central part of Iran, during two seasons. Fungi genera and bacteria species are recognized by cultivation. Concentrations of bacteria and fungi were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Comparing these findings with other studies, we found significant differences in fungal concentrations reported in critical hospital environments. Nasiri et al (2021) investigated the microbiological air quality in different hospital wards (NICU and Surgical center) and found that the mean concentrations obtained for each environment were much lower than those found by us. Likewise, Mirhoseini et al (2020) and Montazeri et al (2020) reported fungal concentrations in critical hospital areas that ranged from 0 to 63 CFU/m³ and 7 to 92 CFU/m³ respectively, and mean concentrations that were also below that found in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Comparing these findings with other studies, we found significant differences in fungal concentrations reported in critical hospital environments. Nasiri et al (2021) investigated the microbiological air quality in different hospital wards (NICU and Surgical center) and found that the mean concentrations obtained for each environment were much lower than those found by us. Likewise, Mirhoseini et al (2020) and Montazeri et al (2020) reported fungal concentrations in critical hospital areas that ranged from 0 to 63 CFU/m³ and 7 to 92 CFU/m³ respectively, and mean concentrations that were also below that found in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License that the occurrence of HAI is more than two folds higher in the developing world (Nasiri et al, 2021;Nejad et al, 2011). The hospital environment serves as an essential reservoir for various infectious microorganisms.…”
Section: Introductionmentioning
confidence: 95%
“…In this study, bacterial concentrations in hospital environments were not significantly related to relative humidity, but fungal concentration was correlated to relative humidity. 25 All the aforementioned studies have highlighted the influence of environmental factors on bioaerosol concentration. However, these studies do not focus on the dispersion of bioaerosol under different environmental factors.…”
Section: Introductionmentioning
confidence: 99%